Incidence of Acute Achilles Repair Surgeries in the Peri-Pandemic COVID Era: And Parallels to the Current 2021-22 NFL Season. Issue 4 (November 2022) - Azam, Mohammad T.; Bi, Andrew S.; Alaia, Michael J.; Jazrawi, Laith M.; Gonzalez-Lomas, Guillem; Kennedy, John G.
Category: Sports; Ankle Introduction/Purpose: The World Health Organization declared the outbreak of COVID-19 a pandemic on March 11, 2020, leading to lockdowns, quarantines, and increased sedentary behaviors. As the general population as well as athletes returned to their normal physical activities or sport in 2021, the risk for musculoskeletal injury increases after inactivity. Thus, the purpose of this study was (1) to investigate the rates of AATR requiring repair in a single academic center in NYC, and (2) see if a corollary exists in the NFL. Our hypothesis is that after a decrease in AATRs in 2020 from decreased physical activity due to a combination of lockdown sanctions and COVID pandemic-induced fears, there is a rebound increase in AATRs in 2021, possibly even to greater than pre-pandemic levels. Methods: All study protocols were approved by the Institutional Review Board at the senior author's institution. A retrospective search was conducted using current procedural terminology to identify the total number of Achilles acute primary repair surgeries performed from years 2017 to 2021 at a sincle academic center. NFL data was obtained from publicly available sites according to previously validated studies. Chi-square analysis was conducted between proportion of Achilles surgeries performed in 2021 and 2017-2020 at a single academic center. Additional Chi-square analysis was performed in a similar manner, however between each year and 2021. Results: A total of 588 patients who sustained AATRs and underwent primary surgical repair were identified, primarily men (75.7%, n = 445), with an average age of 43.22+-14.4 years. The incidence of the total number of AATR repairs per year was: 2017: 21.1% (n = 124), 2018: 18.7% (n = 110), 2019: 22.1% (n = 130), 2020: 14.6% (n = 86), 2021: 23.5% (n = 138), indicating a 7.5% decrease in rate of AATRs from 2019 to 2020, followed by an 8.9% increase in incidence from 2020 to 2021. Within the NFL, the number of AATRs resulting in an IR stint increased every regular season from 2019-2020: 21.2% (n = 11), to 2020-2021: 32.7% (n = 17), to this past 2021-2022 season: 46.2% (n = 24). Conclusion: The main finding of our study is a decrease in the incidence of AATRs during the height of the COVID pandemic quarantine in 2020, with a 8.9% increase in 'post-COVID' 2021 at a single academic institution. There was also a 2.9% higher incidence of AATR in 2021 compared to 'pre-COVID' normal levels when averaged between 2017 to 2019, findings that are mirrored in the NFL. This information provides important information for providers when counseling patients and athletes on return to sport in this current pandemic, especially with possible future lockdowns or quarantines due to new variants such as Omicron.